2021
DOI: 10.1111/joid.12204
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Learning Styles of Interior Design Students in Generation Z

Abstract: Numerous generations are found in today's classroom ranging from Baby Boomer and Generation X instructors to Millennial and Generation Z students. While Generation Z comprises almost 80% of the student population among accredited interior design programs, little is known about their knowledge acquisition. Thus, the purpose of this study was to investigate the dominant learning styles among undergraduate interior design students of Generation Z. Following the work of Watson and Thompson, the Gregorc Style Delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Visual designers communicate ideas and information through a variety of media, using both traditional tangible skills and strategic design thinking to establish credibility and effectively influence target audiences in design and marketing contexts [1][2][3]. In the meantime, Albadi et al [4] and Martins et al [5] reported that the concept of visual design encompasses a broader spectrum, including posters, typography, illustration, web design, packaging design, and visual identity design, all of which find application in various sectors within the creative industries. Also, Huang [6] presented new perspectives on the positioning and capability needs of the visual design industry in the post-epidemic era.…”
Section: Introductionmentioning
confidence: 99%
“…Visual designers communicate ideas and information through a variety of media, using both traditional tangible skills and strategic design thinking to establish credibility and effectively influence target audiences in design and marketing contexts [1][2][3]. In the meantime, Albadi et al [4] and Martins et al [5] reported that the concept of visual design encompasses a broader spectrum, including posters, typography, illustration, web design, packaging design, and visual identity design, all of which find application in various sectors within the creative industries. Also, Huang [6] presented new perspectives on the positioning and capability needs of the visual design industry in the post-epidemic era.…”
Section: Introductionmentioning
confidence: 99%
“…(Lazányi & Bilan, 2017). Generation Z is active in constant digital communication (Albadi & Zollinger, 2021).…”
Section: Introductionmentioning
confidence: 99%